MANFAAT PENERAPAN STRATEGI DIGITAL SINGLE MARKET (DSM) DI KAWASAN UNI EROPA TAHUN 2015–2018 - Purnawan, Putri Andini; Intan Paraeswari, Anak Agung Ayu; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This study aims to analyze the benefits of Digital Single Market implementation in EU during the period of this implementation from 2015 to 2018 using a qualitative method. Along with the development of digital technology, there is a will from European Union as a regional organization to update strategies in the field of trade. On the other hand, the European Union has several obstacles related to the previous strategy, it is the Single Market strategy which makes it difficult for some transactions thatt can affect economic integration. This new strategy, namely the Digital Single Market (DSM) as one of the efforts of the European Union to increase its economic integration by obtaining several benefit. These benefits are increasing the flow of trade in the EU, increasing digital facilities in the EU, and reducing barriers to trade. This answer is obtained through the concept of economic integration and Digital Single Market. Keywords : Digital Single Market (DSM), European Union, Economic Integration, Digital Trade